Degradation of methylene blue by natural manganese oxides: kinetics and transformation products. Issue 7 (10th July 2019) - Zhou, Shuangxi; Du, Zhiling; Li, Xiuwen; Zhang, Yunhai; He, Yide; Zhang, Yongjun
Abstract : In this study, natural manganese oxides (MnO x ), an environmental material with high redox potential, were used as a promising low-cost oxidant to degrade the widely used dyestuff methylene blue (MB) in aqueous solution. Although the surface area of MnO x was only 7.17 m 2 g −1, it performed well in the degradation of MB with a removal percentage of 85.6% at pH 4. It was found that MB was chemically degraded in a low-pH reaction system and the degradation efficiency correlated negatively with the pH value (4–8) and initial concentration of MB (10–50 mg l −1 ), but positively with the dosage of MnO x (1–5 g l −1 ). The degradation of MB fitted well with the second-order kinetics. Mathematical models were also built for the correlation of the kinetic constants with the pH value, the initial concentration of MB and the dosage of MnO x . Furthermore, several transformation products of MB were identified with HPLC-MS, which was linked with the bond energy theory to reveal that the degradation was initiated with demethylation.